Thematic Mapping for Operations Management: An Analysis Based Editorial Space Offer By Scientific Magazines and Conferences in This Field (REGE Revista de Gestão, 2013)
The practice of mapping themes according to recommended topics to potential authors by international refereed journals has been used in many research papers in Operations Management. Regardless of the methods and approaches used to classify the themes related to Operations Management, and the judgments that may be made based on them, it is important that such initiatives be carried out. Reflection about what is regarded as important by journals and conference proceedings in the area represent a first step for further reflection on what is really important for the Operations Management academic community. Thus, the purpose of this paper is to identify the themes that are valued in Operations Management in the context of Business Administration, based on the availability of editorial space in the main national and international academic journals and conference proceedings. The resulting mapping may be useful for understanding the most valued themes by editors and scientific committees and for monitoring the mainstream of studies on Operations Management in Brazil and in the world.